Association of Arterial Stiffness with Chronic Kidney Disease: A Systematic Review - Angela L. Beros; John D. Sluyter; Robert Scragg (Karger Publishers, 2024)
Introduction: Significant kidney function may be lost before CKD is diagnosed. Arterial stiffness may be a risk factor for CKD and the relationship may be bi-directional. A systematic review of cohort studies was undertaken to ascertain the temporal relationship of arterial stiffness and CKD. Methods: MEDLINE and Embase were searched to 4 October 2023 to identify studies that investigated whether arterial stiffness, as estimated by pulse wave velocity, was predictive of the development or progression of CKD, rapid decline in kidney function, and vice versa. The characteristics and outcomes of the included studies were set out in a qualitative summary. The review protocol is registered with PROSPERO (CRD42019129563). Results: Forty-two studies were included, all of which were high quality with respect to bias. Thirteen of seventeen studies that investigated arterial stiffness as a predictor of incident CKD found a positive association (p < 0.05). Of the 10 studies that controlled for CKD risk factors, 6 found a positive association. Eight of seventeen studies that investigated arterial stiffness as a predictor of progression of CKD, and five out of eight studies, which investigated rapid kidney decline, found a positive association. One study of six found kidney function was able to predict future elevated arterial stiffness. Conclusion: Arterial stiffness may predict incident CKD and a rapid decline in CKD. It is uncertain if arterial stiffness is associated with CKD progression or whether reduced kidney function is predictive of increased arterial stiffness. Further longitudinal research is required.